Initial Psychometric Testing and Validation of the Italian Version of the Canine Brief Pain Inventory in Dogs With Pain Related to Osteoarthritis - della Rocca, Giorgia; Di Salvo, Alessandra; Medori, Cristina; della Valle, Maria Federica; Cimino Brown, Dottie (Frontiers in Veterinary Science, 2021)
The Canine Brief Pain Inventory (CBPI) is an owner-administered questionnaire, originally developed and validated in English, used to assess canine chronic pain in terms of severity and interference with daily life activities. The aim of the present study was to perform a preliminary validation of an Italian version of the CBPI. Translation was performed and the resulting questionnaire was administered to 45 native Italian speaking owners of dogs suffering from chronic pain due to radiographically confirmed osteoarthritis. Psychometric properties of the Italian CBPI including construct validity, convergent validity and reliability were evaluated. Construct validity was assessed by factor analysis and confirmed a two-factor model (i.e., pain severity and interference factors). The respective scores, i.e., the pain severity score (PSS) and pain interference score (PIS), exhibited a substantial negative correlation with overall quality of life score. Pain severity and interference items showed a mean inter-item correlation of 0.90 and 0.80, respectively. For each question, communality ranged from 0.84 to 0.97, highlighting strong internal consistency and suggesting that PSS and PIS can be calculated by averaging the items contained within each factor. Cronbach’s α was 0.97 and 0.96 for PSS and PIS, respectively. The present findings confirmed the main psychometric properties of the Italian version of the CBPI, providing clinicians and researchers with a useful metrology instrument to evaluate the severity of chronic pain and its interference with daily life activities in dogs with osteoarthritis owned by Italian speaking people. Further properties of the questionnaire need to be evaluated in future research and larger studies are warranted.